1953
DOI: 10.1085/jgp.36.3.327
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Study of in Vivo Survival of Limited Populations of Animal Red Blood Cells Tagged With Radioiron

Abstract: Until recently, only a few studies (1-6) of red cell life span in a limited number of animal species had been made. These early studies, made by a variety of methods, gave estimates of red cell life span for certain species that varied widely (e.g. rabbit 8 to 42 days, dog 20 to 124 days). Recently, Finch and coworkers (7) employing radioiron, and Bale et al. (8) employing C a* have estimated the life span of the dog red cell to be 107 to 110 and 115 days, respectively. Harrison and associates (9) using radioi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1954
1954
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…In these same animals, when the rate of change of plasma iron during the first 3 h of study was used, an even better correlation with the proportion of early release was observed (Fig. 3) A significantly better correlation was observed when early release is related to the rate of change in plasma iron (P < 0.001) than to the level of plasma iron (P < 0.01 (18,19) and a blood volume of 90 ml/ kg (20). Despite the fact that the normal rate of erythrocyte iron turnover was exceeded, a more than 10-fold increase of the iron load to above 100 Ag/kg produced no apparent difference in the pattern (2) where a single injection of 100 Ag nitrilotriacetic acid iron 3 h before injection of WDRBC was found to markedly depress the immediate release of RE iron and to proportionately increase the radioiron incorporation into ferritin.…”
Section: Resultsmentioning
confidence: 85%
“…In these same animals, when the rate of change of plasma iron during the first 3 h of study was used, an even better correlation with the proportion of early release was observed (Fig. 3) A significantly better correlation was observed when early release is related to the rate of change in plasma iron (P < 0.001) than to the level of plasma iron (P < 0.01 (18,19) and a blood volume of 90 ml/ kg (20). Despite the fact that the normal rate of erythrocyte iron turnover was exceeded, a more than 10-fold increase of the iron load to above 100 Ag/kg produced no apparent difference in the pattern (2) where a single injection of 100 Ag nitrilotriacetic acid iron 3 h before injection of WDRBC was found to markedly depress the immediate release of RE iron and to proportionately increase the radioiron incorporation into ferritin.…”
Section: Resultsmentioning
confidence: 85%
“…If the same holds true for the dog, whose normal erythrocyte life span is about 100 days (22), the slow exponential type of decay curve of PNP activity over a period of about 70 days depicted in Figure 5 suggests that the increased PNP activity remained in the rapidly produced cells of the dog for the duration of their survival. SUMMARY 1.…”
Section: Discussionmentioning
confidence: 83%
“…for 45 mins. and correcting the resulting figure for the 3 per cent of the saline that had been shown to be trapped among the corpuscles under our conditions (4). The radioactivity of the red cell suspension was measured in a well type scintillation counter 2 after diluting 1: 100 with distilled water.…”
Section: Methodsmentioning
confidence: 99%